Okręg Wilno Armii Krajowej .......... 445 - Chudzicka, Joanna (Kresowi żołnierze Armii Krajowej: Historia – Polityka – Pamięć, 2024)
HOME ARMY VILNIUS DISTRICTThe article focuses on the history of the Vilnius District of the Home Army (Armia Krajowa, AK) during World War II. It presents the formation process and activities of the District from the creation of the first underground organizations in September 1939 to the execution of Operation “Ostra Brama” in 1944, aimed at liberating Vilnius and being part of the “Burza” (Tempest) operation. The article describes the mobilization of the Vilnius District AK forces and their preparations for action. Additionally, the text analyzes the organizational structure of the District, the size and development of partisan units, the changing conditions of occupation, and the impact of these events on underground activities. The repressions of the District’s members after 1944 and their impact on changes in the structure and activities of the underground are also discussed. The article aims to delve into the history and significance of the Vilnius District AK in the context of Poland’s struggle for independence during World War II.